Limited duration of antiarrhythmic drug use for newly diagnosed atrial fibrillation in a nationwide population under age 65. (3rd April 2021) - D'Angelo, Robert N.; Rahman, Motiur; Khanna, Rahul; Yeh, Robert W.; Goldstein, Laura; Yadalam, Sashi; Kalsekar, Iftekhar; Tung, Patricia; Zimetbaum, Peter J.
Abstract: Introduction: Antiarrhythmic drugs (AADs) are commonly used for the treatment of newly diagnosed symptomatic atrial fibrillation (AF), however initial AAD choice, duration of therapy, rates of discontinuation, and factors associated with a durable response to therapy are poorly understood. This study assesses the initial choice and duration of antiarrhythmic drug therapy in the first 2 years after diagnosis of AF in a younger, commercially insured population. Methods: A large nationally representative sample of patients age 20–64 was studied using the IBM MarketScan Database. Patients who started an AAD within 90 days of AF diagnosis with continuous enrollment for 1‐year pre‐index diagnosis and 2 years post‐index were included. A Cox proportional hazards model was used to determine factors associated with AAD discontinuation. Results: Flecainide was used most frequently (26.8%), followed by amiodarone (22.5%), dronedarone (18.3%), sotalol (15.8%), and propafenone (14.0%), with other AADs used less frequently. Twenty‐two percent of patients who started on an AAD underwent ablation within 2 years, with 79% discontinuing the AAD after ablation. Ablation was the strongest predictor of AAD discontinuation (hazard ratio [HR], 1.70; 95% confidence interval [CI]: 1.61–1.80), followed by the male gender (HR, 1.10; CI: 1.02–1.19). Older patients (HR, 0.76; CI: 0.72–0.80; reference age 18–49) and those with comorbidities, including cardiomyopathy (HR, 075; CI: 0.61–0.91), diabetes (HR, 0.83; CI: 0.75–0.91), and hypertension (HR, 0.87; CI: 0.81–0.94) were less likely to discontinue AADs. Conclusion: Only 31% of patients remained on the initial AAD at 2 years, with a mean duration of initial therapy 7.6 months before discontinuation.